Access to upper levels: Its impact on achievement at the primary level - Miller, Errol L. (1990)
This article examines the effect of access to the upper levels of the Jamaican educational system (affecting opportunities of upward mobility) on achievement at the lower levels. It also considers the related effect on traditional patterns of achievement, for example boys out-performing girls
Keywords: Academic achievement